Substantiation of the model of formation of students' motivation for scientific activity in the conditions of a university of a physical education - Saikina E.G. ,; Fokin A.M. ,; Kuzmina S.V.,; Lupanova E.S., (Theory and Practice of Physical Culture, 2023)
Objective of the study was to theoretically substantiate and develop a model for the formation of motivation for research activities of students of physical education universities, to determine its prospects and operating conditions. Methods and structure of the study. The logic of the study is based on activity-based (direction of the content of funds depending on priority professional tasks) and systemic approaches. The following was carried out: literature analysis, pedagogical observations, questionnaires, etc., which made it possible to theoretically substantiate and develop a model for the formation of student motivation for research activities. Results and conclusions. A model for the formation of motivation for scientific activity of students of physical education universities has been theoretically substantiated and developed; the structure, purpose, objectives, operating conditions and prospects for its implementation in higher education institutions have been determined. The role of the student scientific association based on self-government is revealed and a step-by-step algorithm for attracting students to research activities is presented.